Linear Regression to Analyze Temperature and Air Humidity on Rainfall: A Case Study at Padang Panjang Geophysics Station (2020-2023) - Lovia, Lita; Yessy Yusnita; Alona Dwinata (Department of Mathematics, Universitas Negeri Padang (UNP), 2024)
This study aims to analyze the correlation between temperature, humidity, and Rainfall at the Geophysics Station of Padang Panjang from 2020 to 2023. Monthly data from the Meteorology, Climatology, and Geophysics Agency (BMKG) was used to evaluate the relationship between these meteorological variables. Statistical analysis, including correlation and multiple linear regression, was conducted using SPSS version 22. The results show a significant negative correlation between Rainfall and temperature, indicating that temperature tends to decrease as rainfall increases. In contrast, a positive correlation between Rainfall and humidity suggests that higher humidity levels are associated with increased Rainfall. However, the regression analysis reveals that temperature and moisture explain only 16.76% of the variation in Rainfall, indicating the potential influence of other factors not included in the model.